Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/antiox11020318
|View full text |Cite
|
Sign up to set email alerts
|

Bone Regeneration and Oxidative Stress: An Updated Overview

Abstract: Bone tissue engineering is a complex domain that requires further investigation and benefits from data obtained over past decades. The models are increasing in complexity as they reveal new data from co-culturing and microfluidics applications. The in vitro models now focus on the 3D medium co-culturing of osteoblasts, osteoclasts, and osteocytes utilizing collagen for separation; this type of research allows for controlled medium and in-depth data analysis. Oxidative stress takes a toll on the domain, being b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 169 publications
(186 reference statements)
0
25
0
Order By: Relevance
“…It is showed that the expression of COL1A1 gene was significantly higher in ferrcluster B and gencluster B compared with ferrcluster A and gencluster A, respectively, while there is no statistical difference in term of VDR gene, COL1A2 genes, and PTH gene expressions between ferrcluster A and B, together with gencluster A and B. OP is a polygenic and complex disease, and future studies should pay attention to the gene-to-gene association, and multiple genes should be considered comprehensively in exploring the mechanism of OP, so as to provide a genetic basis for early clinical screening of OP patients and determination of high-risk groups for fracture, this will facilitate early and effective prevention and treatment of OP. Current research on OP has focused on iron overload and reactive oxygen species (ROS) production, but the intrinsic link between ferroptosis and OP has not been thoroughly investigated ( 43 ). Chinese herbal medicines are potentially valuable in the treatment of OP, and herbal components (artesunate ( 44 ), quercetin ( 45 ), etc.…”
Section: Discussionmentioning
confidence: 99%
“…It is showed that the expression of COL1A1 gene was significantly higher in ferrcluster B and gencluster B compared with ferrcluster A and gencluster A, respectively, while there is no statistical difference in term of VDR gene, COL1A2 genes, and PTH gene expressions between ferrcluster A and B, together with gencluster A and B. OP is a polygenic and complex disease, and future studies should pay attention to the gene-to-gene association, and multiple genes should be considered comprehensively in exploring the mechanism of OP, so as to provide a genetic basis for early clinical screening of OP patients and determination of high-risk groups for fracture, this will facilitate early and effective prevention and treatment of OP. Current research on OP has focused on iron overload and reactive oxygen species (ROS) production, but the intrinsic link between ferroptosis and OP has not been thoroughly investigated ( 43 ). Chinese herbal medicines are potentially valuable in the treatment of OP, and herbal components (artesunate ( 44 ), quercetin ( 45 ), etc.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, ROS are known to adversely affect bone homeostasis and fracture healing [ 5 , 38 ]. As Nrf2 protects cells against ROS exposure [ 39 ] it may not surprise that the expression of Nrf2-target genes is decreased in female KO mice [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is a normal process, and it helps tissue regeneration. However, the long-term production of ROS by high levels of phagocytic cells may cause the opposite effect-implant rejection, dangerous pathological conditions related to protein and DNA damage, which leads to impaired cell function and even resorption of surrounding tissues [54]. Slika et al noticed the high antioxidant potential of the polyphenols inhibits the formation of ROS [55].…”
Section: Cell Studiesmentioning
confidence: 99%
“…This is due to the presence of hydroxyl groups on the benzene rings. Antioxidants, by catching the free radical, give away a hydrogen atom or an electron, which is the transfer of a proton, resulting in a stable molecule and radical derived from an antioxidant [54]. Cellular studies conducted by Dziadek et al (2021) using macrophages have shown that the production of reactive oxygen species is lower when cells are cultured in contact with films enriched with polyphenols [37].…”
Section: Cell Studiesmentioning
confidence: 99%